2015
DOI: 10.1103/physreva.91.061804
|View full text |Cite
|
Sign up to set email alerts
|

Photon antibunching from few quantum dots in a cavity

Abstract: Single quantum dots (QDs) are frequently used as single-photon sources, taking advantage of the final exciton decay in a cascade that produces energetically detuned photons. We propose and analyze a new concept of single-photon source, namely, a few-QD microcavity system driven close to, but below the lasing threshold under strong excitation. Surprisingly, even for two or three QDs inside a cavity, antibunching is observed. To quantify the results, we find that a classification of single-photon emission in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
(65 reference statements)
1
17
0
Order By: Relevance
“…2c show an anti-bunching regime that exists for a large region of the pump and extends from nano-to macroscopic lasers with β = 1. Anti-bunching has been observed in an experiment with a high cavity Q micropillar containing N ≈ 15 pumped quantum dots [23] and in numerical simulations of quantum dot nanocavities [6], [24]. The observation is consistent with our prediction (Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…2c show an anti-bunching regime that exists for a large region of the pump and extends from nano-to macroscopic lasers with β = 1. Anti-bunching has been observed in an experiment with a high cavity Q micropillar containing N ≈ 15 pumped quantum dots [23] and in numerical simulations of quantum dot nanocavities [6], [24]. The observation is consistent with our prediction (Fig.…”
supporting
confidence: 90%
“…pled from the perturbations of the slow variables allowing us to determine analytically the stability of the nonlasing state (see SM Eqs. (22)(23)(24)). The non-lasing state is stable for c † c < c † c th and unstable for c † c > c † c th where…”
mentioning
confidence: 99%
“…In semiconductor experiments a light source is said to emit SPs if the second-order correlation function g (2) (τ) fulfills g (2) (0)<1/2 [15]. This criterion is widely used in the semiconductor optics literature for the last 20 years [14][15][16][17][18][19][20][21]. Throughout this time, the information gained from this quantity has varied a lot, ranging from single emitters [15][16][17] to SPs, from a quantitative interpretation as in [20] to a downplay of this quantification as in [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…This criterion is widely used in the semiconductor optics literature for the last 20 years [14][15][16][17][18][19][20][21]. Throughout this time, the information gained from this quantity has varied a lot, ranging from single emitters [15][16][17] to SPs, from a quantitative interpretation as in [20] to a downplay of this quantification as in [18,22]. There is significant research in trying to lower g (2) (0) further towards ideal zero, see [19] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the second-order correlation function of photons emitted by coupled QD qubits can be utilized as a "witness" of quantum entanglement formation; specifically, antibunching of photons emitted by the QDs has been numerically predicted [25]. Various QD coupling methods have been proposed including sharing the photon field in an optical microcavity [26] or the interactions with auxiliary plasmonic nanoantennas [14][15][16][17]. However, direct observations of the entanglement of electronic degrees of freedom in QDs remain challenging.…”
Section: Introductionmentioning
confidence: 99%